Feasibility of awake craniotomy in the pediatric population. Issue 4 (13th February 2020) - Alcaraz García‐Tejedor, Gabriela; Echániz, Gastón; Strantzas, Samuel; Jalloh, Ibrahim; Rutka, James; Drake, James; Der, Tara
Abstract: Background: Awake craniotomy with direct cortical stimulation and mapping is the gold standard for resection of lesions near eloquent brain areas, as it can maximize the extent of resection while minimizing the risk of neurological damage. In contrast to the adult population, only small series of awake craniotomies have been reported in children. Aims: The aim of our study is to establish the feasibility of awake craniotomy in the pediatric population. Methods: We performed a retrospective observational study of children undergoing a supratentorial awake craniotomy between January 2009 and April 2019 in a pediatric tertiary care center. Our primary outcome was feasibility of awake craniotomy, defined as the ability to complete the procedure without conversion to general anesthesia. Our secondary outcomes were the incidence of serious intraoperative complications and the mapping completion rate. Results: Thirty procedures were performed in 28 children: 12 females and 16 males. The median age was 14 years (range 7‐17). The primary diagnosis was tumor (83.3%), epilepsy (13.3%), and arterio‐venous malformation (3.3%). The anesthetic techniques were asleep‐awake‐asleep (96.7%) and conscious sedation (3.3%), all cases supplemented with scalp block and pin‐site infiltration. Awake craniotomy was feasible in 29 cases (96.7%), one patient converted to general anesthesia due to agitation. Serious complications occurred in six patients: agitation (6.7%), seizures (3.3%), increased intracranial pressure (3.3%), respiratory depression (3.3%), and bradycardia (3.3%). All complications were quickly resolved and without major consequences. Cortical mapping was completed in 96.6% cases. New neurological deficits occurred in six patients (20%)—moderate in one case and mild in 5—being all absent at 6 months of follow‐up. Conclusion: Awake craniotomy with intraoperative mapping can be successfully performed in children. Adequate patient selection and close cooperation between neurosurgeons, anesthesiologists, neuropsychologists, and neurophysiologists is paramount. Further studies are needed to determine the best anesthetic technique in this population group.